Fuzzy logic speed controller for DC motor / Ezamil Radi Halil - Halil, Ezamil Radi (2006)
Today, there are many types of DC motor controller that had been designed. Engineers had designed new methods of speed control, which improve the performance of the motor. Motor controllers are important especially to DC motor where they are used currently in many industries. DC motors have several variable characteristics and are used extensively in variable speed drives. They are also can provide a high starting torque and also possible to obtain speed control over wide range. The methods of speed control are normally simpler and less expensive than those of AC drives.